A Presence without a Narrative: The Greeks in Egypt, 1961-1976 - Eftychia Mylona (Revue des Mondes Musulmans et de la Méditerranée)
This paper examines the upward social mobility of the Greek community in Egypt from the implementation of Gamal Abdel Nasser’s Nationalization Laws of 1961 up until the introduction of the infitah policies of Anwar Sadat in 1976. Both Greek and Egyptian historiographies ceased to explore the activities of the Greek community that remained in Egypt following the massive departure of Greeks in 1961-1962. Instead, they focus mainly on the Greek benefactors and the important social and economic capital they provided when the community was at its demographic peak. Additionally, they focus on Nasser’s policies, in particular the growth of Arab national-ism and the implementation of the Nationalization Laws. This focus overlooks the actual social mobility experienced by the lower and middle-class Greeks who remained in Egypt and evolved socially. What’s more this social mobility calls into question the construction of a homogeneous social and economic post-colonial Egyptian state.